The Role of Non-Mycorrhizal Fungi in Germination of the Mycoheterotrophic Orchid Pogoniopsis schenckii Cogn. - Sisti, Laís Soêmis; Flores-Borges, Denisele Neuza Aline; Andrade, Sara Adrián López de; Koehler, Samantha; Bonatelli, Maria Letícia; Mayer, Juliana Lischka Sampaio (Frontiers in Plant Science, 2019)
Endophytic microorganisms are those that inhabit the internal part of organs and tissues of plants without causing damage to the host, while fungi that develop a hyphal complex (pelotons) within cortical cells of orchid roots are called orchid mycorrhizal fungi. Approximately 235 species of orchids remain aclorophyllated throughout their life cycle, being totally dependent on their mycorrhizal partners for carbon compounds, and these plants are known as mycoheterotrophic (MH). Pogoniopsis schenckii Cogn. is an aclorophyllated and MH species that grows under organic matter in dense tropical forests. This study was aimed generally at (i) investigating the endophytic fungal community of organs of P. schenckii and mycorrhizal fungi; (ii) evaluating the role of isolated fungus in the in vitro germination of the seeds of the species, and (iii) describing the development of the protocorm, analyzing the ultrastructure of infected cells. Thus, the endophytic fungi present in the roots, floral stem and fruits were isolated and identified through partial sequencing of the ITS region, as well as the non-cultivated mycorrhizal fungi. In addition, the isolated fungi were used in trials of symbiotic germination with orchid seeds, and the protocorm structure was analyzed by different anatomical techniques. Six genera of fungi were isolated and identified, being all belonging to the phylum Ascomycota, and throught uncultured technique Tulasnellaceae was identified as potentially mycorrhizal. Some isolates of the genera Trichoderma, Fusarium and especially Clonostachys presented germinative potential on the seeds of P. schenckii, causing rupture of the external seed tegument. The protocorms analyzed by transmission electron microscopy showed no pelotons formation, but fungal hyphae were observed occupying the interior of the living cells. This is the first report of germination of a MH and aclorophyllated orchid species stimulated by the presence of non-mycorrhizal endophytic fungi isolated from fruits and roots.